Rapid Identification of Intact Staphylococcal Bacteriophages Using Matrix-Assisted Laser Desorption Ionization-Time-of-Flight Mass Spectrometry - Štveráková, Dana; Šedo, Ondrej; Benešík, Martin; Zdráhal, Zbyněk; Doškař, Jiří; Pantůček, Roman (Viruses, 2018)
Staphylococcus aureus is a major causative agent of infections associated with hospital environments, where antibiotic-resistant strains have emerged as a significant threat. Phage therapy could offer a safe and effective alternative to antibiotics. Phage preparations should comply with quality and safety requirements; therefore, it is important to develop efficient production control technologies. This study was conducted to develop and evaluate a rapid and reliable method for identifying staphylococcal bacteriophages, based on detecting their specific proteins using matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) profiling that is among the suggested methods for meeting the regulations of pharmaceutical authorities. Five different phage purification techniques were tested in combination with two MALDI-TOF MS matrices. Phages, either purified by CsCl density gradient centrifugation or as resuspended phage pellets, yielded mass spectra with the highest information value if ferulic acid was used as the MALDI matrix. Phage tail and capsid proteins yielded the strongest signals whereas the culture conditions had no effect on mass spectral quality. Thirty-seven phages from Myoviridae, Siphoviridae or Podoviridae families were analysed, including 23 siphophages belonging to the International Typing Set for human strains of S. aureus, as well as phages in preparations produced by Microgen, Bohemia Pharmaceuticals and MB Pharma. The data obtained demonstrate that MALDI-TOF MS can be used to effectively distinguish between Staphylococcus-specific bacteriophages.
Keywords: chemická frakcionace; stafylokokové bakteriofágy; Cluster Analysis; replikace viru; Staphylococcus aureus; virové proteiny; shluková analýza; MALDI-MS; Kayvirus; bacteriophages; Staphylococcus Phages; Biological Products; Viral Proteins; Staphylococcus; Viral proteins; phage therapy; lidé; Virus Replication; Humans; Chemical Fractionation; spektrometrie hmotnostní - ionizace laserem za účasti matrice; biologické přípravky; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization